Genome-Wide SNPs Provide Insights on the Cryptic Genetic Structure and Signatures of Climate Adaption in Amorphophallus albus Germplasms - Gao, Yong; Yin, Si; Chu, Honglong; Zhang, Yanan; Wang, Haibo; Chen, Huanhuan; Liu, Chao; Dai, Dongqin; Tang, Lizhou (Frontiers in Plant Science, 2021)
Domesticated species represent unique systems in which the evolutionary genomic consequences of intensive selective breeding and adaptation can be thoroughly investigated. Amorphophallus albus occurs naturally and is in cultivation throughout the downstream region of the Jinshajiang River in Southwest China. This species is characterized by high konjac glucomannan content, and has been cultivated in China for nearly 2,000 years. To study genetic differentiation and local adaption of A. albus, we sampled 13 distinct local cultivated populations of this species. Restriction site-associated DNA sequencing was conducted with 87 samples, resulting in 24,225 SNPs. The population structure analyses suggest two main genetic groups: one in the relatively upstream region, and one downstream. We found evidence of additional sub-structure within the upstream group, demonstrating the statistical power of genomic SNPs in discovering subtle genetic structure. The environmental and geographic factors were all identified as significant in shaping the genetic differentiation of this species. Notably, the proportion of environmental factors was larger than geographic factors in influencing the population genetic patterns of A. albus. We also discovered loci that were associated with local adaptation. These findings will help us understand the genetic differentiation of this newly domesticated species, thereby informing future breeding programs of A. albus.